Moxibustion for primary dysmenorrhea: A resting-state functional magnetic resonance imaging study exploring the alteration of functional connectivity strength and functional connectivity - Yang, Han; Li, Xiang; Guo, Xiao-li; Zhou, Jun; Shen, Zhi-fu; Liu, Li-ying; Wei, Wei; Yang, Lu; Yu, Zheng; Chen, Jiao; Liang, Fan-rong; Yu, Si-yi; et al. (Frontiers in Neuroscience, 2022)
Introduction: Primary dysmenorrhea (PDM) is a common gynecological disease and chronic pain disorder. Moxibustion, a form of traditional Chinese medicine therapy, has been proved to be effective for PDM. However, the central mechanisms of PDM and moxibustion for PDM are still unclear. The aim of this study was to explore the potential central mechanism of PDM and clarify the possible mechanism of moxibustion for relieving pain. Methods: 23 PDM patients and 23 matched healthy controls (HCs) were enrolled. For PDM patients, resting-state functional magnetic resonance imaging (rs-fMRI) data was collected pre- and post-moxibustion treatment of 3 consecutive menstrual cycles, respectively. For HCs, rs-fMRI data was collected in the baseline. The resting-state functional connectivity strength (rs-FCS) analysis and the resting-state functional connectivity (rs-FC) analysis based on the region of interest (ROI) were combined to be conducted. Results: Compared to HCs, PDM patients showed weaker rs-FCS in the left inferior frontal gyrus (IFG). After moxibustion treatment, rs-FCS in the left IFG was increased with clinical improvement. Then, the left IFG was chosen as ROI, and the rs-FC analysis was conducted. It showed that the left IFG rs-FC in the bilateral anterior cingulate cortex (ACC)/ middle cingulate cortex (MCC), the left posterior cingulate cortex (PCC)/ pre-cuneus (PCU), and the left parahippocampal gyrus (PHG) decreased after moxibustion treatment, most of which belong to the default mode network (DMN). Conclusions: Our results highlight the role of the left IFG and the DMN in PDM. Specifically, the central mechanism of moxibustion for analgesia may be related to modulate the disorders of the reappraisal and processing of pain stimuli through influencing the cognition of pain.